Odpowiedzi

2010-03-07T22:13:29+01:00
I)6x+8y-12=0
-3x-4y+6=0

6x=-8y+12
-3x-4y=-6

x=-4/3y+2
-3*(-4/3y+2)-4y=-6

x=-4/3y+2
4y-3/2-4y=-6

x=-4/3y+2
-3/2=-6

układ nie ma rozwiązania
II)4y=-8+6x
-3x+2y=-2

y=-2+3/2x
-3x+2*(-2+3/2x)=-2

y=-2+3/2x
-3x-4+3x=-2

y=-2+3/2x
-4=-2

układ nie ma rozwiazania
2010-03-07T22:15:55+01:00
I)
6x+8y-12=0
-3x-4y+6=0

6x+8y=12
-3x-4y=-6|:(-3)

6x+8y=12
x=2+4/3y

6(2+4/3y)+8y=12
12+8y+8y=12
16y=0
y=0

x=2+4/3*0
x=2+0
x=2


II)
4y=-8+6x|:4
-3x+2y=-2

y=-2+1,5x
-3x+2(-2+1,5x)=-2
-3x-4+3x=-2
0=2